Dampak Pembelajaran Bilingual Sejak Dini Terhadap Perkembangan Anak Usia Batita - Widiasari, Linda (CV Insan Kreasi Media, 2024)
The ability to speak two languages, also known as bilingualism, is an extraordinary advantage in an increasingly globalized world. However, the implementation of bilingual education for young children remains a topic that sparks debate and diverse perspectives. The purpose of this study is to analyze the impact of early bilingual education on the development of toddlers (children under three years old). This research was conducted using a literature review method, referencing various sources and findings from the internet over the past 10 years. The results reveal that early bilingual education has positive effects on children's cognitive, social, and linguistic development, such as enhancing critical thinking skills, memory, and cultural understanding. However, some challenges were also identified, such as the potential for code-mixing and temporary delays in vocabulary development in one of the languages. With the implementation of an appropriate learning framework and support from the surrounding environment, bilingual education can provide a strong foundation for children to face global challenges in the future. This study offers recommendations for parents and educators to optimally implement bilingual education for children.